The Teaching of science and health, mathematics, and home economics, and practical arts - Salandanan, Gloria G.; Santos, Rosita G.; Diaz, Eden C. (Quezon City, Philippines : Katha Publishing Co, Inc., 1996)
STRATEGIES III has been prepared in recognition of the current thrusts in secondary Science, Mathematics, and Livelihood education. It is designed to provide the necessary training and experience in newer and effective approaches and techniques in teaching said subjects. Today, more than at any other time, educators feel the need for equipping pre-service students with competencies that will enable them to meet the fast-changing needs and interests of the youth. This instructional material is intended to prepare this legion of future teachers to cope with such changes.
I. Objectives of Science Education -- II. Effective Procedures in Teaching Science -- III. The Basic Investigative Process -- IV. Evaluating Learning in Science -- V. Trends in Science Education -- VI. Strategies in Teaching Mathematics -- VII. Evaluating Mathematics Learning -- VIII. Preparation of Instructional Materials -- IX. The Teaching of Home Economics and Practical Arts -- X. Instructional Resources in the teaching of Home Economics and Practical Arts -- XI. Evaluating Home Economics and Practical Arts.
Includes bibliographical references.
Keywords: ECONOMICS